EFFECT OF RAINFALL ON THE CHEMICAL COMPOSITION OF RAINWATER IN MONITORING ACID DEPOSITION IN GREATER BANDUNG - Dandy Rievaldo; Indra Chandra; Wiwiek Setyawati; Asri Indrawati; Dyah Aries Tanti; Ardiansyah Ramadhan; Lutfhi Rizqi Mubarok; Tazlila Rahmi Rasyid; Azrina Abd Aziz; Zainal Arid Burhanudin (Universitas Trisakti, 2023)
Aim: The study aimed to investigate the impact of rainwater on the acidity levelsto monitor acid deposition and identify sources of pollutant that affect the acidity concentrations of rainwater. Methodology and Results: One unit of rainwater sampler in each location was employed, andsamples were taken to the National Research and Innovation Agency laboratory (BRIN) for analysis of rainwater quality including acidity/pH degree, conductivity, and ion concentrations. The results show that high rainfall intensity (>300 mm/month) in April and December 2019 led to a decrease in electrical conductivity (<10 mS/cm) and ion compounds (>200 μmol/L) of rainwater, likely due to the dissolution/washing process of anions in the air during the rainy season and acid and alkaline neutralization in the dry season. The most identified chemical compounds were ammonium (NH4+), sulfate (SO42-), nitrate (NO3-), and salt (NaCl). Conclusion, significance, and impact study: Based on back-trajectory projections, the decline in rainwater quality was attributed to both local emissions (transportation, industry, agriculture, and waste burning) and long-range sources (earth crust, oceans, coastlines, marine activities, and anthropogenic and forest fires in the Australian territory).